Brainstorming dalam Pencegahan Pneumonia pada Anak Balita - Islamiyah Iis; Islaeli Islaeli; Sri Wahyuni; Wa Ode Aisa Zoahira; Anisa Purnamasari (Poltekkes Kemenkes Kendari, 2019)
One of the infectious diseases which is the biggest contributor to under-five mortality in Indonesia is pneumonia. In developing countries, pneumonia is called The One Killer Of Children and has become a neglected health problem because many children die from pneumonia but very little attention is paid to handling this problem. Pneumonia is an acute infectious process that affects the lung tissue (alveoli) and can be recognized through guidelines for clinical signs and other investigations. Overcoming pneumonia is not enough just by mastering treatment and handling, but it requires sufficient knowledge about the causes of pneumonia so that preventive efforts can be made to prevent pneumonia in toddlers. Brainstorming health education is one of the factors that influence knowledge. The purpose of this study was to determine the effect of the btanstorming method on the knowledge and attitudes of mothers in preventing pneumonia in children under five. Respondents in this study were mothers of toddlers. The results of this study indicate that there is an increase in knowledge in preventing pneumonia in children under five before and after the intervention. The brainstorming method of health education can change the level of knowledge of mothers at the Abeli ??Community Health Center in preventing pneumonia in children under five to a better direction. The brainstorming method of health education can change the attitudes of mothers at the Abeli ??Community Health Center in preventing pneumonia.